Migration and Spanish Constitution - Pérez González, Carmen (2018)
The Spanish Constitution was adopted in 1978. It contains some articles related to migration issues. According to article 13.1, aliens shall enjoy the rights guaranteed by the Constitution under the terms to be laid down by treaties and the Spanish law. Article 13 refers also to the question of extradition and to the possibility of seeking asylum in Spain. This work aims to determine the scope of these provisions, taking into account both the Constitutional Court’s case law adopted to implement it, and the international obligations assumed by the State. Besides that, the analysis should consider, on the one side, that since the adoption of the Constitution, Spain is not a country of origin of migrants any more, but a country of destination. And, on the other side, the deep impact of the European integration process on migration Spanish law and policy.